Association between hip flexor tightness and lumbar instability in adults - Khan, Asghar; Malik, Arshad Nawaz (Journal of the Pakistan Medical Association, 2023)
The study aimed to explore the association between hip flexors tightness and lumbar instability in adults. The study design was correlational and 64 subjects of both genders (male and female) with age range from 20 to 50 years were selected with a history of low back pain (LBP) with or without referred pain. Two examiners were assigned for application of the Modified Thomas Test (MTT) for hip flexors tightness and lumbar prone Instability Test (LPIT) and Prone Lumbar Extension Tests (PLET) for lumbar instabilities. The numeric pain rating scale (NPRS) was used for pain assessment. The two examiners were not aware of each other’s findings. The lambda value 0.238 which shows there is a weak association between MTT and PLET. The Cramer’s V value 0.179 also shows a weak relationship between MTT and LPIT. This study observed that there is a weak association between tight hip flexors and lumbar instability.